2016
DOI: 10.1093/nar/gkw1040
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Genome Database (MGD)-2017: community knowledge resource for the laboratory mouse

Abstract: The Mouse Genome Database (MGD: http://www.informatics.jax.org) is the primary community data resource for the laboratory mouse. It provides a highly integrated and highly curated system offering a comprehensive view of current knowledge about mouse genes, genetic markers and genomic features as well as the associations of those features with sequence, phenotypes, functional and comparative information, and their relationships to human diseases. MGD continues to enhance access to these data, to extend the scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
299
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(314 citation statements)
references
References 25 publications
5
299
0
Order By: Relevance
“…First, we tested whether the genes identified for each of the four biggest GWAS categories overlapped the most closely corresponding mouse phenotype 19 (e.g., genes found to be associated with autoimmune traits in the present paper and the mouse ''immune system phenotype'') by using a one-sided Fisher's exact test. We additionally listed the high-level mouse phenotypes of the individual trait-associated genes.…”
Section: Gene-set Enrichment Analysismentioning
confidence: 99%
“…First, we tested whether the genes identified for each of the four biggest GWAS categories overlapped the most closely corresponding mouse phenotype 19 (e.g., genes found to be associated with autoimmune traits in the present paper and the mouse ''immune system phenotype'') by using a one-sided Fisher's exact test. We additionally listed the high-level mouse phenotypes of the individual trait-associated genes.…”
Section: Gene-set Enrichment Analysismentioning
confidence: 99%
“…MECOM is specifically expressed in the emerging limb buds in embryogenesis, but insufficient production seems to have no effect on bone development; skeletal abnormalities were not observed in any of the Evi1 knockout models. 35 Furthermore, 2 patients with heteroinsufficiency of the MECOM gene resulting from deletion at chromosome 3q26 did not display RUS. 20,36,37 Niihori et al 6 suggested that the missense mutations identified in their study might act as gain-of-function or partial loss-of-function mutations rather than complete lossof-function mutations.…”
Section: Cd38mentioning
confidence: 97%
“…Species IDs were extracted from National Center for Biotechnology Information (NCBI) (NCBI Resource Coordinators, 2017) Taxonomy browser. Names of human and mouse genes were updated according to the HUGO Gene Nomenclature Committee (HGNC) (Gray, Yates, Seal, Wright, & Bruford, 2015) and Mouse Genome Database (Blake et al., 2017) and others in accordance to NCBI gene nomenclature if available. Gene synonyms used in articles are written in brackets.…”
Section: Methodsmentioning
confidence: 99%